High magnetic field lattice length changes in URu2Si2 - Correa, V.F.; Francoual, S.; Jaime, M.; Harrison, N.; Murphy, T.P.; Palm, E.C.; Tozer, S.W.; Lacerda, A.H.; Sharma, P.A.; Mydosh, J.A.; Correa, Víctor Félix (American Physical Society, 2012)
Fil: Correa, V.F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina